Laguage Morphology and It's Line Features: Awareness, Instruction, Strategies, and Analysis: a Systematic Review - Malaya, Janessa Angustia Martinez (Universitas Muhammadiyah Lampung, 2024)
More and more linguists are becoming interested morphology, particularly in dialectal morphology. A solid theory of word production is a prerequisite for the development of any comprehensive theory of language. However, there are a number of unresolved issues that render any morphological theory weakness due to the lack of evidence-based solutions as some of these issues can be essential to the theory. The acquisition and learning of word formation rules is something else that concerns us, beside tongue morphology awareness, instructions, strategies, and interpretation analysis. As part of the search for papers for this review, a number of electronic databases were scrutinized. All descriptors were used in combination with morphology, awareness, instruction, strategies, and analysis. Ancestral searches were also carried out, and content analysis has been employed developing a goal interpretation of any type of morphological content. Results and discussions are derived in this regard from the researcher’s own undertaking as well as that of other scholars. It is plainly evident that morphology is a bough of linguistics after gathering a total of thirty-four (34) explorations from numerous abstractions and fieldworkers. The study and modeling of language structure are major constituents of linguistics in all of its manifestations, historical evolution, and forms.